Ageing effects on high damping bridge rubber bearing - Gu, Haosheng; Itoh, Yoshito (2006)
In recent years high damping rubber (hdr) material has attracted much attention of technologists because it possesses both flexibility and high damping properties. However, it is also known that rubber performance drops due to the ageing effect. Many problems are still not clear, for example, how does the property of hdr material change over the time, which environmental factor dominates the degradation of hdr, in what way does ageing progress from the surface to the interior of the hdr bearing, and what influence does ageing produce on the mechanical performance of hdr bridge bearing. In order to solve these problems, in this study a series of accelerated exposure tests are carried out on hdr pieces and blocks. Firstly, different degradation factors such as thermal oxidation, ultraviolet, ozone, low temperature ozone, salt water and acid rain are applied to hdr specimens. The property variations are examined and the thermal oxidation is found to be the predominant degradation factor. Then, thermal oxidation tests are performed on hdr blocks at various elevated temperatures and the development of the property profiles is investigated. An aging model for hdr bearing is developed to predict the mechanical behaviors at any position inside the bearing. Next, based on the predicted material properties, fem analysis is carried out using the constitutive law. Finally, the long-term performance of aged hdr bearing is clarified. Using the arrhenius methodology, the test conditions may be transformed to the real environment, so that the future performance a hdr bridge bearing may be estimated with the site condition taken into consideration.